If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3x + 1) = 3x + -9X Reorder the terms: 6(1 + 3x) = 3x + -9X (1 * 6 + 3x * 6) = 3x + -9X (6 + 18x) = 3x + -9X Reorder the terms: 6 + 18x = -9X + 3x Solving 6 + 18x = -9X + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6 + 18x + -3x = -9X + 3x + -3x Combine like terms: 18x + -3x = 15x 6 + 15x = -9X + 3x + -3x Combine like terms: 3x + -3x = 0 6 + 15x = -9X + 0 6 + 15x = -9X Add '-6' to each side of the equation. 6 + -6 + 15x = -6 + -9X Combine like terms: 6 + -6 = 0 0 + 15x = -6 + -9X 15x = -6 + -9X Divide each side by '15'. x = -0.4 + -0.6X Simplifying x = -0.4 + -0.6X
| 1/4x+4=y | | y^3=-21 | | -12x+2(x-5)+9x=3x-10 | | x+y=15andx-2 | | -3.5=x/7 | | 8b-9y/4b-b-5y/4b | | b-9y/4b-b-5y/4b | | 8b-9y/4b-b-5y/4b=0 | | 2x^3-1-1=0 | | 20+3m+6m=92 | | -52^1/2 | | 11/2d=8 | | 1/5(10x-4)=7 | | -11/2d | | (4x+15)+(-5+2x)+(-10+6x)=360 | | 144/2 | | -[6z-(17z+9)]=9+(10z+1) | | 0=24x^3+20x^2-54x-45 | | 10+25=-5(9x-7) | | 2x-8y-9x+6y= | | 5x+5=49 | | (x-7)(x^2+10x+16)=0 | | 39x+52-14x-35=5x-13 | | (x-6)(x^2+9x+20)=0 | | 3x=16-1 | | 5x^2+25=-20 | | -16x^2+24x+50=0 | | 0.5(x-1/3) | | -2/-3d=8 | | (r-3)/10=r/16 | | -3(6y-7)-y=-4(y-5) | | 2x+4-5(x+1)=5x+6 |